Studi Komparasi Sektor E-commerce pada Awal dan Akhir Pandemi Covid-19 - Radias Kartika Utami; Muhammad Akmal Perdana; Tazkiratul Hamda; Siti Rahmah; Dewi Anggraini; Selvi Annisa (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Publikasi (LPPMP), 2025)
This study examines the impact of the COVID-19 pandemic on the e-commerce sector in Indonesia by comparing its growth at the beginning and end of the pandemic. COVID-19 was first detected in Wuhan, China in December 2019 and became a global pandemic in March 2020. The pandemic affected various sectors, including the economy and business, with some sectors like e-commerce experiencing growth. This study uses a quantitative method with secondary data from